Foreshadows and Symbols in The Brussels Companyâs Main Office in Joseph Conradâs Heart of Darkness - Ena, Ouda Teda; Yulia, Made Frida (LLT Journal: A Journal on Language and Language Teaching, 2012)
Joseph Conradâs Heart of Darkness unveils a story about a journey to the inner selfto find the mysteries of human mind. The way the writer presents his story is veryintriguing in that he makes of use of many foreshadows and symbols. This paperattempts to examine the foreshadows and symbols which Conrad uses in this novella;Â however, the discussion is limited to the ones that appear in The Brussels CompanyâsÂ Main Office.Â DOI: https://doi.org/10.24071/llt.2012.150202